ESTIMATION OF GENETIC VARIABILITY AND ASSOCIATION AMONG DIFFERENT PHYSIOLOGICAL TRAITS RELATED TO BIOTIC STRESS (F USARIUM OXYSPORUM L.) IN CHICKPEA - M. Aslam; M. A. Maqbool; S. Akhtar; W. Faisal (Journal of Animal and Plant Sciences, 2013)
Experiment was conducted to assess genetic differences among chickpea genotypes under normal and biotic stress (inoculated with Fusarium oxysporum L.) conditions, to estimate the relationship among different biotic stress related traits and to identify suitable parental material to be used in breeding programs for the development of genotypes resistant to fusarium wilt. The responses of 70 different chickpea genotypes were evaluated on the basis of different physiological traits by following principal component analysis (PCA). According to PCA, under normal and stress conditions out of eight only 4 PCs had more than one eigen value in each case and collectively contributed 71.50% and 75.2% variability under normal and stress conditions respectively. Biplot analysis depicted that under normal condition the genotypes 1007, 60101, 7008, 405, PB91, B3008, 3013, 7002, 7012, 1217, 6011, BITAL98, 6028 and CH-8 were highly diversified, whereas under stress condition, genotypes 7059, 4004, 6001, 7046, 1288 and 1143 proved resistant and presented the greatest diversity. Genotypes 6028, 7027, BRC236, 5028, 7056-1, 6010, 6003, 1217, 3013, 4028¸ 6017, 7010, 3019, PB2000, 5006, 6255, 4046, PB2008, B3008, 1159, 2009-1, and 6011 were found with least diversity and declared as susceptible because of poor performance.
Keywords: Chickpea; Fusarium wilt; Biplot; PCA and Correlation